1976
DOI: 10.1115/1.3450516
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in Enclosed Spaces—A Review of Application to Solar Energy Collection

Abstract: A useful solar-thermal converter requires effective control of heat losses from the hot absorber to the cooler surroundings. Based upon the theory and some experimental measurements it is shown that the spacing between the tilted hot solar absorber and successive glass covers should be in the range 4–8 cm to assure minimum gap conductance. Poor choice of spacing can significantly affect thermal conversion efficiency, particularly when the efficiency is low or when selective black absorbers are used. Recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(55 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…To estimate of the convective heat transfer coefficient between the absorber plate and glass cover h pg , the following three-region correlation of Buchberg et al [21] where Ra (= Ra cos β) is Rayleigh number for the inclined air layers between the absorber plate and glass cover (collector slope β = 0 • for horizontal). The Rayleigh number is given by…”
Section: Top Lossmentioning
confidence: 99%
“…To estimate of the convective heat transfer coefficient between the absorber plate and glass cover h pg , the following three-region correlation of Buchberg et al [21] where Ra (= Ra cos β) is Rayleigh number for the inclined air layers between the absorber plate and glass cover (collector slope β = 0 • for horizontal). The Rayleigh number is given by…”
Section: Top Lossmentioning
confidence: 99%
“…Buchberg et al [25] have suggested the following correlation (18) for solving the natural convection heat transfer coefficient in the enclosed space between the absorber plate and glass cover.…”
Section: Knudsen Numbermentioning
confidence: 99%
“…Studies include thermal stability and heat transfer of inclined honeycomb cells, e.g., reports by Randall et al (1977) and Buchberg et al (1976). Attention is focused primarily in trying to minimize convection in order to prevent heat losses.…”
Section: F Gas Conductionmentioning
confidence: 99%